Social Security and Endogenous Demographic Change: Child Support and Retirement Policies - Giam Pietro Cipriani; Tamara Fioroni (Institute of Labor Economics (IZA), 2021)
This paper studies retirement and child support policies in a small, open, overlapping-generations economy with PAYG social security and endogenous retirement and fertility decisions. It demonstrates that neither fertility nor retirement choices necessarily coincide with socially optimal allocation, because agents do not take into account the externalities of fertility and the elderly labor supply in the economy as a whole. It shows that governments can realize the first-best allocation by introducing a child allowance scheme and a subsidy to incentivize the labor supply of older workers. As an alternative to subsidizing the elderly labor supply, we show that the first-best allocation can also be achieved by controlling the retirement age. Finally, the model is simulated in order to study whether the policies devoted to realizing the social optimum in a market economy could be a Pareto improvement.
Keywords: D10; H2; H55; J13; J18; J26; 330; PAYG pensions; social security; endogenous fertility; endogenous retirement